Application of optical character recognition in thermal image processing - Chan, W.T.; Sim, K.S.; Tso, C.P. (ELSEVIER, 2011)
This paper presents the results of a study on the reliability of the thermal imager compared to other devices that are used in preventive maintenance. Several case studies are used to facilitate the comparisons. When any device is found to perform unsatisfactorily where there is a suspected fault, its short-fall is determined so that the other devices may compensate, if possible. This study discovered that the thermal imager is not suitable or efficient enough for systems that happen to have little contrast in temperature between its parts or small but important parts that have their heat signatures obscured by those from other parts. The thermal imager is also found to be useful for preliminary examinations of certain systems, after which other more economical devices are suitable substitutes for further examinations. The findings of this research will be useful to the design and planning of preventive maintenance routines for industrial benefits. (C) 2011 Elsevier B.V. All rights reserved.